2005
DOI: 10.1080/02713680590934111
|View full text |Cite
|
Sign up to set email alerts
|

Human Cathelicidin (LL-37), a Multifunctional Peptide, is Expressed by Ocular Surface Epithelia and has Potent Antibacterial and Antiviral Activity

Abstract: Purpose: This study determined whether LL-37 (cathelicidin)is expressed by conjunctival and corneal epithelia as part of ocular host defense. The antimicrobial activity of LL-37 was also assessed in vitro against Pseudomonas aeruginosa (PA), Staphylococcus aureus (SA), Staphylococcus epidermidis (SE), herpes simplex virus type 1 (HSV-1), and adenovirus (Ad). Methods: Expression of LL-37/hCAP 18 mRNA and LL-37 protein was determined by reverse transcription-polymerase chain reaction (RT-PCR) and immunoblotting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
190
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(207 citation statements)
references
References 73 publications
12
190
1
2
Order By: Relevance
“…In our current study, we measured HSV replication by evaluating glycoprotein D gene expression using real-time RT-PCR. By directly measuring the virus activity rather than cellular proliferation, it provides a more direct and appropriate measurement of the anti-viral activity of LL-37 against HSV accounting for differences between our results and those of Yasin et al 15 Our observation is further supported by Gordon et al 16 who recently demonstrated that LL-37 exhibits anti-viral activity against HSV-1 in corneal and conjunctival epithelia.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our current study, we measured HSV replication by evaluating glycoprotein D gene expression using real-time RT-PCR. By directly measuring the virus activity rather than cellular proliferation, it provides a more direct and appropriate measurement of the anti-viral activity of LL-37 against HSV accounting for differences between our results and those of Yasin et al 15 Our observation is further supported by Gordon et al 16 who recently demonstrated that LL-37 exhibits anti-viral activity against HSV-1 in corneal and conjunctival epithelia.…”
Section: Discussionsupporting
confidence: 82%
“…AD skin is characterized by the over-expression of the Th2 cytokines IL-4 and IL-13. 16 Previously we demonstrated that Th2 cytokines down-regulate cathelicidin. 10 However, due to the difficulty in identifying ADEH patients and insufficient amounts of archived tissue, we were unable to investigate the levels of IL-4 and IL-13 in AD and ADEH patients for potential differences.…”
Section: Discussionmentioning
confidence: 98%
“…Although assays were less sensitive for VEE, detection limits for VEE in the AMP-based assays were similar to or better than those of competing cell-or antibodybased technologies [21,22,24,25]. Several groups have previously described the antiviral effects of various AMPs and their derivatives on vaccinia virus [26][27][28]. Most relevant to the present study is a cecropin Amagainin-2 hybrid peptide (CA (1-8)-MA(1-12)) which was shown to exhibit antiviral effects in other studies [26].…”
Section: Discussionmentioning
confidence: 99%
“…It has direct microbicidal activities against a wide range of bacteria, viruses, fungi, and protozoa in vitro (5)(6)(7)(8)(9)(10). In addition, its antimicrobial functions in vivo are significantly contributed by multiple immunomodulatory properties (11)(12)(13).…”
mentioning
confidence: 99%